Efektivitas pendekatan saintifik dalam meningkatkan kemampuan berpikir kritis matematis siswa kelas 8 pada materi persamaan garis lurus - Zahran, Deliya; Maya, Rippi; Zanthy, Luvy Sylviana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This study aims to examine the mathematical critical thinking ability of students who obtain a Scientific Approach compared to those who obtain ordinary learning. The method used in this research is the experimental method. The research subject in this study were students of SMPN 9 Cimahi, who were randomly selected from two classes out of all 8 grades. Then two classes were randomly assigned to become the experimental class and the control class. The experimental class gets learning with a Scientific Approach and the control class gets regular learning. The instrument used is a test of mathematical critical thinking skills. From the results of the data analysis it was concluded that an increase in the ability to think critically mathematically of students who received a Scientific Approach was better than those who received regular learning.